Weight loss maintenance strategies among rural breast cancer survivors: The rural women connecting for better health trial. Issue 10 (1st September 2016) - Befort, Christie A.; Klemp, Jennifer R.; Sullivan, Debra K.; Shireman, Theresa; Diaz, Francisco J.; Schmitz, Kathryn; Perri, Michael G.; Fabian, Carol
Abstract : Objective: Obesity is a risk factor for breast cancer recurrence. Rural women have higher obesity rates compared with urban women and are in need of distance‐based interventions that promote long‐term weight loss. Methods: In this two‐phase trial, rural breast cancer survivors who lost >5% of their starting weight during a 6‐month lifestyle intervention (delivered through weekly group conference calls) were randomized to one of two 12‐month interventions for weight loss maintenance: continued biweekly phone‐based group counseling or mailed newsletters. The primary outcome was weight regain from 6 to 18 months. Secondary outcomes included dichotomous measures of weight change and costs. Results: Mean weight loss at 6 months was 14.0 ± 5.1%. Participants in the group phone condition regained less weight (3.3 ± 4.8 kg) compared with participants in the newsletter condition (4.9 ± 4.8 kg; P = 0.03). At 18 months, 75.3% of participants in the group phone condition remained ≥5% below baseline weight compared with 57.8% in the newsletter condition ( P = 0.02). Incremental cost‐effectiveness ratios were $882 to keep one more person ≥5% below baseline weight. Conclusions: A lifestyle intervention incorporating group phone‐based support improved the magnitude of weight loss maintained and increased the proportion of survivors who maintained clinically significant reductions.